Maximization of fixed carbon content in biochar applied to carbon sequestration - Roz, Alessandra L. da; Ricardo, Jose F. C.; Nakashima, Gabriela T.; Santos, Luis R. O. [UNESP]; Yamaji, Fabio M. [UNESP] (Univ Federal Campina Grande, 2015)
Currently, the emission of carbon dioxide is the main cause of global warming due to greenhouse effect. Researchers around the world have been studying to find viable solutions to the problem. Biochar is among the latest proposals for mitigating climate change due to its simplicity and efficiency. Therefore, this study aimed to maximize the fixed carbon content in the production of biochar. Seven treatments were analysed with pyrolysis temperature of 200, 250, 300, 350, 400, 450 and 500 degrees C. From the production yield and fixed carbon content, the gravimetric yield factor was calculated for each treatment, which indicates the amount of fixed carbon. The pyrolysis temperature of 300 degrees C showed the greatest gravimetric yield factor, reaching 0.22672 C/biochar.
Keywords: pyrolysys; Eucalyptus; gravimetric yield factor